2002
DOI: 10.1164/rccm.2105141
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Combined Intravenous and Topical Antibiotic Prophylaxis on the Incidence of Infections, Organ Dysfunctions, and Mortality in Critically Ill Surgical Patients

Abstract: We prospectively studied the impact of an antibiotic prophylaxis regimen on the incidence of infections, organ dysfunctions, and mortality in a predominantly surgical and trauma intensive care unit (ICU) population. A total of 546 patients were enrolled and stratified according to Acute Physiology and Chronic Health Evaluation (APACHE)-II scores. They were then randomized to receive either 2 x 400 mg of intravenous ciprofloxacin for 4 days, together with a mixture of topical gentamicin and polymyxin applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
116
0
22

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 271 publications
(141 citation statements)
references
References 60 publications
3
116
0
22
Order By: Relevance
“…While often recommended, it appears not to be routinely practiced. Two recent studies will further the debate, as they demonstrated significant reductions in VAP and mortality with selective decontamination of the digestive tract (47,114). These two studies were performed under conditions where selective decontamination of the digestive tract is most effective, i.e., surgical intensive care units housing patients less likely to be colonized with resistant bacteria.…”
Section: Preventionmentioning
confidence: 99%
“…While often recommended, it appears not to be routinely practiced. Two recent studies will further the debate, as they demonstrated significant reductions in VAP and mortality with selective decontamination of the digestive tract (47,114). These two studies were performed under conditions where selective decontamination of the digestive tract is most effective, i.e., surgical intensive care units housing patients less likely to be colonized with resistant bacteria.…”
Section: Preventionmentioning
confidence: 99%
“…1,2 Although there is still controversy regarding the universal indication of SID for critical care patients, in 5 of 9 published meta-analyses and in 4 recent randomized studies not included in a previous meta-analysis, a reduction in the mortality related to SID administration could be demonstrated in patients admitted to intensive care units (ICUs), mostly when systemic antibiotics were administered. [1][2][3][4][5][6] Bacterial infections (especially those involving gram-negative bacteria) are major complications for liver transplant recipients (LTRs); their frequency ranges from 20% to 80%. They contribute substantially to longer hospital stays and increased hospital costs 7 and are the leading cause of death in this population.…”
mentioning
confidence: 99%
“…Despite their excellent efficacy, broad antibacterial spectrum and good tolerability, cephalosporins, which rapidly induce drug-resistant bacteria, are arguably not the ideal drugs for preventive therapy [70,71]. Previous studies on prophylactic antibiotic treatment in other settings did not support the assumption that short-term prophylactic antibiotic drug treatments facilitate the development of antibiotic drug resistance [38,72]. However, if antibiotic prophylaxis should be implemented into the daily routine of stroke units, and large numbers of patients would be treated with the same antibiotic drugs within a single ward, the development of drug resistance could constitute a point of concern.…”
Section: Discussionmentioning
confidence: 99%